Comparative Study of FNAC and Histopathology in Diagnosis of Thyroid Swelling - Rahman, Md Mukhlesur; Begum, Mahmuda; Majumder, Dhananjoy (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2023)
Background: Neck swelling is a common clinical presentation in ENT practice and it carries significant morbidity and even mortality if not managed properly. Thyroid swelling being the most common type among them. We conducted a study to assess the role of FNAC in diagnosing the nature of thyroid swelling and comparing its result with histopathology finding. The aim and objectives of this study is to observe the correlation between preoperative Fine Needle Aspiration Cytology (FNAC) and post operative histopathology in the diagnosis of thyroid lesions. Materials and methods: A cross sectional study was done in the Department of Otolaryngology-Head & Neck Surgery and Department of Pathology, Chittagong Medical College, Chattogram from January 2018 to December 2020. Eighty (80) patients, both male and female of different age groups were included. The selected patients were subjected to clinical examination, routine hematological investigation, thyroid hormone test, USG, thyroid Scan, FNAC and histopathological examinations of the thyroidectomy specimens. Correlation between FNAC and histopathology reports were done in those patients. Results: In this study, age range of the patients were 11 years to 70 years. Out of 80 patients of thyroid swelling, the most of the patients 28(35%) were 31-40 years of age groups. out of 80 patients of thyroid swelling, 26(26.25%) were male and 59(73.75%) were female and male female ratio was1:2.81. On FNAC 64(80%) were non neoplastic and 16(20%) were neoplastic. Out of 64(80%) of non neoplastic lesions, 62(77.50%) were nodular goitre and 2(2.5%) were lymphocytic thyroiditis and out of 16(20%) neoplastic thyroid swelling, 2(2.50%) were follicular lesion, 12(15%) were papillary carcinoma, 1(1.25%) was follicular carcinoma and 1(1.25%) was suspicious for malignancy. On histopathology, out of 80 patients of thyroid swelling 60(75%) were non neoplastic and 20(25%) were neoplastic. out of 60(75%) non neoplastic, 59 (73.75%) were nodular, 1(1.25%) was Lymphocytic thyroiditis and out of 20(25%) neoplastic lesions, 3(3.75%) were follicular adenoma,13(16.25%) were papillary carcinoma,3(3.75%) were follicular variant of papillary carcinoma and 1(1.25%) was follicular carcinoma. Conclusion: It is concluded from the present study that female are more affected in our region. Non neoplastic lesions of the thyroid were more common (Nodular goitre being the commonest) than neoplastic lesions (Papillary carcinoma being the commonest). FNAC is essential diagnostic tool for thyroid swelling but final diagnosis to rule out thyroid cancer is surgical excision and histopathology. Chatt Maa Shi Hosp Med Coll J; Vol.22 (1); January 2023; Page 19-22